Hubungan antara Analitics Data Perusahaan dengan Kinerja Perusahaan Meta Platforms Instagram - Syarifah Aini Br Sinaga; Nabila Anisa Risca Lubis; Nurriadoh Nurriadoh; Nurbaiti Nurbaiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the relationship between data analytics utilization and the performance improvement of Meta Platforms Inc., particularly through its Instagram platform. In the digital era, data has become a strategic asset that enables companies to understand user behavior, optimize marketing strategies, and develop innovative products and services. Using a qualitative case study approach, this research illustrates how Meta leverages Instagram analytics—through audience segmentation, campaign effectiveness evaluation, and user insight-driven feature development—to enhance operational efficiency and profitability. The findings show that the use of data analytics not only increases advertising effectiveness and return on investment (ROI) but also strengthens Meta’s position as an innovation leader in the social media industry. The study also highlights the importance of data transparency and ethical practices in data usage, and recommends the development of more open and adaptive data infrastructure to meet evolving user needs.